Collective bargaining and the battle of ohio the defeat of senate bill 5 and the struggle to defend the middle class - McNay, John T.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
The story of how the Ohio conference of the American Association of University Professors mobilized its resources and fought alongside Teamsters, firefighters, janitors, and police to defeat Ohio Senate Bill 5 by referendum, restoring collective bargain rights across the state.
Keywords: Science; Science; Science, general